Current Opinion on Molecular Characterization for GBM Classification in Guiding Clinical Diagnosis, Prognosis, and Therapy - Zhang, Pei; Xia, Qin; Liu, Liqun; Li, Shouwei; Dong, Lei (Frontiers in Molecular Biosciences, 2020)
Glioblastoma (GBM) is highly invasive and the most deadly brain tumor in adults, characterized by substantial inter-tumor and intra-tumor heterogeneity, short survival, and lack of effective treatment. Current molecular analysis tends to apply multiple data from transcription, genetic alterations and DNA methylation to predict patient prognosis and guide therapy. Proneural, neural, classical, and mesenchymal are distinct GBM subtypes classified by transcription, which are widely accepted and used for diagnosis, classification and targeted treatment, and are closely related to other subtypes based on genetic alterations and DNA methylation. In this review, we summarize the principal molecular classification in GBM and its advantages in various aspects, such as supplementary in pathology diagnosis, prognosis prediction, and guide in treatment.